2017
DOI: 10.1080/16549716.2017.1386932
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with childbirth services provided in public health facilities: results from a cross- sectional survey among postnatal women in Chhattisgarh, India

Abstract: Background: A woman’s satisfaction with childbirth services can have a significant impact on her mental health and ability to bond with her neonate. Knowing postnatal women’s opinions and satisfaction with services makes the services more women-friendly. Indian women’s satisfaction with childbirth services has been explored qualitatively, or by using non-standard local questionnaires, but scientific data gathered with standardised questionnaires are extremely limited. Objective: To measure postnatal Indian wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 55 publications
7
57
1
2
Order By: Relevance
“…Results of a cross-sectional survey on 1004 women in India indicated that improving interpersonal interaction with nurse-midwives, and ensuring privacy during childbirth and the hospital stay are recommended first steps to improve women's childbirth satisfaction [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a cross-sectional survey on 1004 women in India indicated that improving interpersonal interaction with nurse-midwives, and ensuring privacy during childbirth and the hospital stay are recommended first steps to improve women's childbirth satisfaction [15].…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire was developed by the author after a massive review of literature which included two main parts: sociodemographic and obstetrical characteristics such as age, educational level, occupation, residency, parity, history of abortion, sex of the baby, admission of the baby to the ICU and 28 items related to verbal (16 items) and non-verbal (12 items) communication of physicians and midwives in delivery room [13][14][15][16][17][18].…”
Section: Data Collectionmentioning
confidence: 99%
“…In general, patients expected their health care providers to keep up timing , behave cordially, and communicate in the patient's native language [11]. They expected care, concern, and courtesy in addition to professionalism [11]. A patient's favorable attitudes toward their doctor were related to the patient's health status [19].…”
Section: Discussionmentioning
confidence: 99%
“…It affects the timely, efficient, and patient-centered delivery of quality health care. Patient satisfaction is thus a proxy but a very effective indicator to measure the success of doctors and hospitals [11].…”
mentioning
confidence: 99%
“…Favourable ratings for client satisfaction and client perception surveys is a well-known phenomenon (21) and has been observed across the world (22)(23)(24). where environmental attributes have been rated negatively in comparison to other attributes (27).…”
Section: Socio Demographic and Pregnancy Related Details Of The Partimentioning
confidence: 99%